Genomic insights into multidrug-resistant Acinetobacter baumannii strains isolated from Dhaka, Bangladesh - Sadia Ferdous; K M Shayerul Abedin Shayer; Afia Anjum; Sabbir R. Shuvo; Ishrat Jabeen; Kristi Paul Hridi; A.K.M. Imrul Hassan; Md Imran Khan; Mohammad Fazle Alam Rabbi; Mahmud Hossain; Kazi Nadim Hasan; Sohidul Islam (Journal of Advanced Biotechnology and Experimental Therapeutics)
Acinetobacter baumannii is one of the most common nosocomial infections causing pathogens. Multidrug-resistant (MDR) A. baumannii is a growing concern to the healthcare system in Bangladesh, necessitating the elucidation of the genetic characteristics of this species. Five MDR, biofilm-forming A. baumannii strains isolated from clinical samples in Dhaka, Bangladesh, underwent a comprehensive whole-genome shotgun sequencing. In silico analyses determined strain types, antibiotic resistance, and virulence genes. The phylogenomic and pan-genome comparative analysis included the study samples along with an additional 15 Bangladeshi A. baumannii strains collected from the public database. The antibiotic-resistant profile showed that all the strains were resistant to meropenem. Two strains were resistant to polymyxin B up to 64 µg/ml. The average draft genome size of the strains was 3.93 Mbp, with about 39% GC content. Multilocus sequence typing characterized the strains as ST1, ST2, ST164, and ST623. All strains carried different classes of β-lactamase genes, including the carbapenem hydrolyzing enzyme coding genes blaoxa-23 and blaoxa-51. One of the five strains studied harbored blaNDM-9 and blaNDM-23 genes. The phosphotransferase group of aminoglycosides modifying enzymes was the most common. All the strains had relatively similar virulence profiles. Pan-genome analysis revealed 1944 core and 1302 unique genes. Phylogenomic analysis revealed the distribution of these strains in different clusters with other MDR strains isolated worldwide. The study results suggest the implementation of antibiotic stewardship and genomic surveillance of MDR A. baumannii to control the spread of antibiotic resistance in Bangladesh. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 64-78]